Statistical optimization of process conditions for direct bioconversion of sewage treatment plant sludge for bioethanol production - Alam, Md. Zahangir; Kabbashi, Nassereldeen Ahmed; Razak, A.A. (2006)
The production of bioethanol was conducted by utilizing domestic wastewater sludge as major substrate with the aid of yeast, Saccharomyces cerevisiae using liquid state bioconversion method (submerged fermentation). The optimi-zation of process conditions such as temperature, initial pH, inoculum dosage and agitation was carried out by using the central composite design (CCD) formulated by a statistical optimization software MINITAB. Optimization of process conditions was done with different ranges of temperature, pH, inoculum sizes and agitations with fixed media compositions obtained from previous study. A polynomial regression model was developed to determine the optimum compositions. Sever-al techniques such ANOVA, t-test, p-values were observed to evaluate the model as well as the optimization process. The maximum ethanol production (9.1% v/v) was found while model equation predicted ethanol production with 11.9% v/v using the optimum conditions: temperature of 330C, pH of 7, agitation of 200 rpm and inoculum of 1%. The results indicat-ed that the temperature was highly significant (p<0.01) fol-lowed by the pH (p<0.01), inoculum (p<0.05) and agitation rate (p<0.05). The coefficient of determination (R2) was 90.1% which satisfied the adjustment of experimental data in the model.